2015
DOI: 10.1002/mar.20794
|View full text |Cite
|
Sign up to set email alerts
|

Change Their Choice! Changing Behavior Using the CAN Approach and Activism Research

Abstract: Most of our research on eating behavior has no impact on health or public policy. Part is due to the nontranslational way we often conduct our studies; part is due to us not having a useful framework that organizes our conclusions. This paper's first purpose is to offer an organizing framework that shows how nearly all effective interventions on food choice either make healthy choices more convenient (physically or cognitively), more attractive (comparatively or absolutely), or more normal (perceived or actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 108 publications
0
67
0
3
Order By: Relevance
“…Participants also indicated that, while motivated to improve their diet, it would be challenging to simply increase the ratio of beans to rice because it would reduce the pleasure associated with eating; thus, recommendations to increase seasoning variety to make eating beans more enjoyable may be well received. Moreover, it would be worth exploring if concomitantly reducing sensory variety in rice, and thereby palatability, may also decrease rice intake and further improve dietary quality [46]. Although reducing sensory variety has not been specifically examined, research suggests that limiting energy-dense food variety can decrease total energy intake and reduce the pleasure associated with consuming these foods [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Participants also indicated that, while motivated to improve their diet, it would be challenging to simply increase the ratio of beans to rice because it would reduce the pleasure associated with eating; thus, recommendations to increase seasoning variety to make eating beans more enjoyable may be well received. Moreover, it would be worth exploring if concomitantly reducing sensory variety in rice, and thereby palatability, may also decrease rice intake and further improve dietary quality [46]. Although reducing sensory variety has not been specifically examined, research suggests that limiting energy-dense food variety can decrease total energy intake and reduce the pleasure associated with consuming these foods [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Influencing the campus environment in these ways has the potential to make the healthy choice the easy choice. 31,38 …”
Section: Implications For Research and Practicementioning
confidence: 98%
“…Boundary research differs from transformative consumer research (Viswanathan, ; Mick, ; Mick et al, ) in that it is not necessarily aimed at improving social welfare, and it differs from activism research (Wansink, , ) in that it does not necessarily need to be translational, practical, or application focused. Within its field, it might adopt or introduce new topics (behavioral economics), new perspectives (post‐positivist explanations), new contexts (eating behaviors), or new methods (content analysis).…”
Section: The Importance Of Boundary Researchmentioning
confidence: 99%